The transposition of directive 2019/1831/EU of October 24, 2019 establishing a fifth list of indicative occupational exposure limit values into national law - Jolanta Skowroń; Lidia Zapór; Katarzyna Miranowicz-Dzierżawska (Nofer Institute of Occupational Medicine, 2022)
The issue of the regulations amending the Regulation of the Minister of Family, Labour and Social Policy on the maximum admissible concentrations and intensities of agents harmful to health in the working environment resulted from the requirement to implement into national law the provisions of Commission Directive (EU) 2019/1831 of 24 October 2019 establishing a fifth list of indicative occupational exposure limit values pursuant to Council Directive 98/24/EC, and amending Commission Directive 2000/39/EC, the provisions of which Member States had to introduce by 20 May August 2021. The Regulation takes into account 3 motions submitted by the Interdepartmental Commission for Maximum Admissible Concentrations and Intensities for Agents Harmful to Health in the Working Environment to the minister of labour in the years 2017-2020. The Commission was appointed by the Regulation of the Prime Minister of December 15, 2008 (Journal of Laws of 2015, item 1772, with amendments), and its tasks include submitting to the minister of labour motions on the value of the maximum admissible concentrations and intensities for agents harmful to health in the working environment. Med Pr. 2022;73(1):43-50